Gametogenic stages in triploid oysters Crassostrea gigas: Irregular locking of gonial proliferation and subsequent reproductive effort - Jouaux, A.; Heude-Berthelin, C.; Sourdaine, P.; Mathieu, M.; Kellner, K. (Journal of Experimental Marine Biology and Ecology, 2010)
International audience Although triploid oysters Crassostrea gigas have generally been considered to be sterile, gametogenesis events are sometimes recorded. We aimed to establish a new classification adapted for the description of gametogenesis in triploid oysters and their comparison with diploid animals. From stage I to stage III, two types of gametogenic pattern were identified: α-pattern, corresponding to animals displaying numerous proliferating gonia (PCNA labelling at stage I), resulting in abundant gametes at stage III and β-pattern, which was associated with locked gametogenesis (only few mature gametes at sexual maturity) with accumulation of abnormal gonia from stage I to III. The granular aspect of TUNEL labelling in the perinuclear area of stage Iα animals suggests either the occurrence of apoptotic events or the possibility of chromosome number regulation (chromosome extrusion).Reproductive effort was evaluated by quantitative approaches in order to evaluate the possible contribution of triploid oysters to recruitment in the natural environment. For mature α triploid animals, the ratio of gonadal area over total area on histological slide preparations reached almost 50% that of diploid counterparts. Moreover, the gonadal area contained numerous mature germinal cells as in diploids. Future ecological studies should consider the involvement of triploids in spat recruitment in the case of spawning by these animals.